2000
DOI: 10.1080/02626660009492324
|View full text |Cite
|
Sign up to set email alerts
|

Real-time flood forecasting with the use of inadequate data

Abstract: A modelling scheme is developed for real-time flood forecasting. It is composed of (a) a rainfall forecasting model, (b) a conceptual rainfall-runoff model, and (c) a stochastic error model of the ARMA family for forecast error correction. Initialization of the rainfall-runoff model is based on running this model on a daily basis for a certain period prior to the flood onset while parameters of the error model are updated through the Recursive Least Squares algorithm. The scheme is suitable for the early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It was found that using k = 4 and a four-step approximation for the trend, an optimal compromise could be found between accurate description of soil moisture variation and number of inputs. This procedure is in line with previous analysis by Nalbantis (2000), who found that the importance of rainfall resolution decreases moving back in time.…”
Section: Data Analysis and Model Set-upsupporting
confidence: 78%
“…It was found that using k = 4 and a four-step approximation for the trend, an optimal compromise could be found between accurate description of soil moisture variation and number of inputs. This procedure is in line with previous analysis by Nalbantis (2000), who found that the importance of rainfall resolution decreases moving back in time.…”
Section: Data Analysis and Model Set-upsupporting
confidence: 78%
“…This method estimates state variables depending on the very last observed discharges. Consequently, the question of initial conditions appears to be less important if some (or even all) states are re-estimated by this updating technique (Nalbantis, 2000;Aubert et al, 2003;Moore et al, 2005).…”
Section: The Real-time Forecasting Specificitiesmentioning
confidence: 99%
“…This is a frequent situation when looking for high time resolution series. To bypass this obstacle, Nalbantis (1995) suggests relying on coarser data series (e.g. daily) to estimate fine (hourly) initial conditions.…”
Section: Continuous Vs Event-based Approaches To Modellingmentioning
confidence: 99%
“…Lekkas et al 2001;Nalbantis 2000;Broersen 2007). The error correction method based on the time series model takes advantage of a tendency in the error sign to persist the sequences of positive (overestimation) or negative errors (underestimation), and it has proven to be more effective and simpler than the Kalman filter updating technique (Nalbantis 2000). Generally speaking, in using the time series models, including the autoregressive (AR) and moving average (MA) models, as well as the associated composite form (ARMA), the suitable order should be identified, which is commonly carried out using Akaike's AIC criterion, in advance.…”
Section: Introductionmentioning
confidence: 97%
“…Hence, the forecast error correction can be carried out by a time series model, such as a autoregressive and moving average (ARMA), which takes advantage of the autocorrelation of the past error (e.g. Lekkas et al 2001;Nalbantis 2000;Broersen 2007). The error correction method based on the time series model takes advantage of a tendency in the error sign to persist the sequences of positive (overestimation) or negative errors (underestimation), and it has proven to be more effective and simpler than the Kalman filter updating technique (Nalbantis 2000).…”
Section: Introductionmentioning
confidence: 99%